THE BENEFITS OF ONLINE COLLABORATIVE LEARNING DURING PANDEMIC: STUDENTS’ VIEWPOINT - Fiorentya, Olgha Caeshar; Puspitasari, Evi (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2021)
Online collaborative learning (OCL) provides students’ communication by gathering with their group to achieve the course’s goals that students have been facing in the Covid-19 pandemic together through online. OCL is the way out to solve the problem when the current circumstances do not allow holding offline group discussions for students. Eventually, there are many benefits that students have been faced by doing OCL during this current situation. Therefore, the researcher wants to investigate the benefits of OCL according to students’ points of view. Descriptive qualitative research was designed for this research to answer the research question by digging deeper into participants’ answers by using interview for collecting the data. The findings of this research showed three benefits of OCL based on students’ points of view. Some students have the flexibility of time and place to hold OCL; students can enhance their technology capability; students can increase their socio-emotional through holding OCL. To sum up, the researcher would inform about the benefits that students and teachers have to be aware more about OCL especially during the Covid-19 pandemic eventually and to support other researchers to arise the same topic.